Impact of state legislation and institutional protocols on opioid prescribing practices following pediatric tonsillectomy - Lisa M. Einhorn; Congwen Zhao; Benjamin A. Goldstein; Sudha R. Raman; Jeffrey Cheng (Laryngoscope Investigative Otolaryngology, 2023)
Abstract Objectives Tonsillectomy is a common pediatric surgery, and pain is an important consideration in recovery. Due to the opioid epidemic, individual states, medical societies, and institutions have all taken steps to limit postoperative opioids, yet few studies have examined the effect of these interventions on pediatric otolaryngology practices. The primary aim of this study was to characterize opioid prescribing practices following North Carolina state opioid legislation and targeted institutional changes. Methods This single center retrospective cohort study included 1552 pediatric tonsillectomy patient records from 2014 to 2021. The primary outcome was number of oxycodone doses per prescription. This outcome was assessed over three time periods: (1) Before 2018 North Carolina opioid legislation. (2) Following legislation, before institutional changes. (3) After institutional opioid‐specific protocols. Results The mean (± standard deviation) number of doses per prescription in Periods 1, 2, and 3 was: 58 ± 53, range 4–493; 28 ± 36, range 3–488; and 23 ± 17, range 1–139, respectively. In the adjusted model, Periods 2 and 3 had lower doses by −41% (95% CI −49%, −32%) and −40% (95% CI −55%, −19%) compared to Period 1. After 2018 North Carolina legislation, dosage decreased by −9% (95% CI −13%, −5%) per year. Despite interventions, ongoing variability in prescription regimens remained in all periods. Conclusion Legislative and institution specific opioid interventions was associated with a 40% decrease in oxycodone doses per prescription following pediatric tonsillectomy. While variability in opioid practices decreased post‐interventions, it was not eliminated. Level of evidence 3